HUBUNGAN FUNGSI KEPEMIMPINAN KEPALA PUSKESMAS DENGAN MOTIVASI KERJA TENAGA KESEHATAN DI PUSKESMAS KEBUN LADA KECAMATAN BINJAI - Ikadawaty Hutabarat; Masryna Siagian; Putranto Manalu (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2019)
Leadership has an influence on the work motivation of health workers in carrying out health services for the community. Based on an initial survey conducted at Kebun Lada Binjai Puskesmas there are still health workers who are lazy at work, often arrive late and go home early, often get together even though working hours are still inadequate, facilities and infrastructure are inadequate such as lack of seats so many patients who stand while waiting for health services, there are still health workers prioritize personal interests rather than the interests of the office in carrying out their duties. Based on the researcher's observations, it was found that the low work motivation of health workers in carrying out their duties and responsibilities. The purpose of this study was to determine the relationship of leadership functions (planning, supervision, and decision making) with the work motivation of health workers. This type of research is an analytic survey research, with cross sectional approach. The population in this study were all health workers as many as 47 people. The method of data analysis uses Chi-square test. The results showed that there was a very significant (strong) relationship between the relationship between planning and workforce motivation of health workers with a value of p = 0,000 or (p <0.05), the relationship of supervision with workforce motivation of workers with a value of p = 0,000 or (p < 0.05), and the relationship between decision making and workforce motivation by health workers with a value of p = 0,000 or (p <0.05). Based on the results of the study it is expected that the Head of the Puskesmas must have the ability to lead subordinates well and be structured in order to carry out health programs well so as to provide work motivation with encouragement and the desire of health workers to carry out an activity or work well.